2012
DOI: 10.1016/j.ultsonch.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonic degradation rates constants of methylene blue at 22.8 kHz, 127 kHz, and 490 kHz

Abstract: Techniques such as solvent extraction, incineration, chemical dehalogenation, and biodegradation have been investigated for the degradation of hazardous organic compounds. We found ultrasound to be an attractive technology for the degradation of hazardous organic compounds in water. However, the effects of ultrasonic frequency on degradation rate constants were not investigated quantitatively. In this study, the degradation process of a model for hazardous organic compound methylene blue was investigated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The optimum appears to occur between 200 and 400 kHz for nonvolatile molecules, while the yield increases for volatile molecules as the frequency increases (Kobayashi et al, 2012;Pétrier and Francony, 1997). …”
Section: The Frequency Effectmentioning
confidence: 99%
“…The optimum appears to occur between 200 and 400 kHz for nonvolatile molecules, while the yield increases for volatile molecules as the frequency increases (Kobayashi et al, 2012;Pétrier and Francony, 1997). …”
Section: The Frequency Effectmentioning
confidence: 99%
“…From the results of our previous study, the apparent rate constant of ultrasonic degradation of methylene blue was evaluated using a pseudo-first-order reaction model [14] [15] [16]. kHz [15].…”
Section: Effect Of Ultrasonic Irradiation Conditions On Methylene Blumentioning
confidence: 99%
“…However, when the frequency is higher than 500 kHz, the value of threshold power of KI oxidation is higher than that of methylene blue degradation, and the difference becomes large with increasing frequency. In our previous study, there is a relationship between SE KI value and degradation rate constant of methylene blue [14] [15] [16]. In addition, it has been reported that the ultrasonic degradation of methylene blue is enhanced by TiO 2 particle addition under dark condition [23] [24] [25], and the presence of TiO 2 particle accelerates the generation of hydroxyl radicals during ultrasonic irradiation even in the absence of UV irradi- ation [26].…”
Section: Effect Of Ultrasonic Irradiation Conditions On Ki Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the advanced chemical oxidation processes, based on the generation of extremely reactive hydroxyl radicals are among the promising techniques for the environmental destruction organic dyes, including MB, in aqueous solution. MB has been oxidized by the generation of hydroxyl radicals using different techniques, among them ultrasonic degradation [11][12][13] and sonophotocatalysis [14][15][16][17] can be mentioned.…”
Section: Introductionmentioning
confidence: 99%